The art of Mozart ensemble in Kazakhstan variety art - Maigaziev, Saken Kordabaevich; Sabirova, Aliya Sultanmuratovna (Opción, 2019)
The purpose of research is to give description of certain provisions from the system of Kazakh traditional ideas about the perfect song, art of performance and peculiarities of sound production. As a method of research we used the empirical and systemic approaches. As a result, the chosen concept for considering musical-aesthetic ideas and beliefs about music allowed to reveal the transformation of aesthetic ideas about music in various historical segments of development. In conclusion, the article considers only one ecocentric type of world picture associated with music.